Study of toxicity of crotalic and bothropic species in ofidic accidents, with an emphasis in renal toxicity - de Castro, Isac (O Mundo da Saúde, 2006)
Ofidic accidents present world lethality of 2.3% and in Brazil reaches 6%. In crotalic and bothropic accidents, acute renal insufficiency (ARI) can ensue caused mainly by acute tubular necrosis (ATN). The main toxic fractions in crotalic venom are crotoxin and A2 phospholipase, whereas bothropic venom consists in metalloproteinases and bothropsin. Crotalic poison can cause glomerular and proximal tubules alterations, and among the main causes of ARI due to ATN is rabdomiolisis, whereas bothropic venom can cause to thrombus formation, causing kidney ischemia due to sanguineous perfusion reduction. Renal compromising because of ofidic accidents, due to presenting systemic compromising, still keeps unclear, as regards the pathogenesis, the venom direct action poison, as well as antiofidic serum therapy, and there is not a clear description about how to reduce the potential direct action of the venom in renal tissue.